The successful pregnancy in patient with Wolff-Parkinson-White syndrome type B - Nicholas Renata Lazarosony; Anak Agung Putra Wiradnyana (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2022)
Background: An aberrant accessory route is a hallmark of the rare heart rhythm condition called Wolff-Parkinson-White (WPW) syndrome. The onset of tachyarrhythmias, which can result in hemodynamic instability and even maternal mortality, is considered to be triggered by a variety of physiological changes that occur during pregnancy. Therefore, it is anticipated that effective management options for pregnant women who have WPW syndrome will be able to regulate tachyarrhythmias and give healthy pregnancies for both the mother and the fetus. Case Report: A 32-year-old pregnant woman with 34 weeks of gestational age arrived complaining of palpitations and breathing difficulties. The results of the ECG test revealed left branch bundle block (LBBB), a Wolff-Parkinson-White (WPW) type B pattern, and sinus tachycardia. Both an NST assessment and an echocardiographic evaluation revealed no fetal distress or structural abnormalities of the heart. The patient was treated with 300 mg of Propafenone, which was administered on a regular basis whenever the patient experienced palpitations. Due to a history of prior caesarean deliveries, the pregnancy had progressed to 40 weeks of gestation and caesarean birth under spinal anaesthesia was performed in this point. The infant was born healthy, full-term, and free from birth problems. Conclusion: One of the causes of tachyarrhythmias in WPW syndrome is pregnancy. Arrhythmias that could develop in women with WPW syndrome can be controlled with good pregnancy planning and management.